Motivation and impact analysis of student marbuts around Universitas Pendidikan Indonesia - Jamaludin, Rafif (Jurnal Abmas, 2026)
The high cost of urban living and the strained social relationships between incoming students and residents around campus are issues that require innovative solutions. Amidst these conditions, student marbut are often viewed as mere mosque guards, even though they have great potential as agents of social change. In this regard, this community service was conducted to examine the dual motivations and socio-religious impacts on student marbut in the neighborhood surrounding the Universitas Pendidikan Indonesia. Using a thematic qualitative approach, data were collected through observation, documentation, and in-depth interviews with four active marbut. The results show that the decision to become a marbut is supported by complementary motivations: intrinsically, through the value of ubudiyah (obligatory worship) and the development of soft skills, and extrinsically, through free housing facilities that serve as hygiene factors, reducing urban financial burdens. Despite facing dual academic and operational burdens, the marbut interpret this role as a social laboratory that fosters independence and resilience. Furthermore, the presence of student marbut has proven capable of revitalizing the social function of mosques, one of which is through interactive Qur’anic teaching that effectively breaks down social distances between communities, thus creating a sustainable mutualistic symbiosis. Based on these findings, a formal strategic partnership between campus and mosque administrators is recommended to strengthen the sustainability of the marbut’s role as an agent of change.